2022
DOI: 10.1108/rjta-01-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life of employees working in the Indian garment industry

Abstract: Purpose The purpose of this study is to identify the level of quality of work life (QWL) of employees working in the Garment industries using a validated scale. Design/methodology/approach Survey methods were used for this study. A questionnaire was designed to collect the data and information, and it is validated through exploratory factor analysis, confirmatory factor analysis. Findings The majority of employees are not satisfied with the present status of QWL in garment units. Followings are the predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
3
2
Order By: Relevance
“…Because in the current study, it was found that GRH positively affects ER only and not JS (H3a). Therefore, the findings on the third hypothesis correspond only to the previous studies inferring that timely and effective grievance redressal leads to high morale and better quality of work life facilitating the attainment of high commitment and ER (Nanjundeswaraswamy and Beloor, 2022;Singla, 2017). However, our results do not support the fact that impartial grievance handling can significantly impact employee job satisfaction (Joseph et al, 2022).…”
Section: Hrp and Er Incontrasting
confidence: 94%
See 2 more Smart Citations
“…Because in the current study, it was found that GRH positively affects ER only and not JS (H3a). Therefore, the findings on the third hypothesis correspond only to the previous studies inferring that timely and effective grievance redressal leads to high morale and better quality of work life facilitating the attainment of high commitment and ER (Nanjundeswaraswamy and Beloor, 2022;Singla, 2017). However, our results do not support the fact that impartial grievance handling can significantly impact employee job satisfaction (Joseph et al, 2022).…”
Section: Hrp and Er Incontrasting
confidence: 94%
“…The fourth and the fifth hypotheses regarding the significant positive effect of HAS and TAD on JS and ER were not supported and they contradict the results of past studies that concluded that better health and safety provisions in an organization (Liu et al, 2019;Poursadeqiyan et al, 2019;Sheikh et al, 2018) or investing in TAD of employees (Armstrong-Stassen and Stassen, 2013;Nanjundeswaraswamy and Beloor, 2022;Ngoma and Ntale, 2019) will lead to JS and ER.…”
Section: Hrp and Er Incontrasting
confidence: 76%
See 1 more Smart Citation
“…Ehido et al (2020) argued that the core focus of QWL is to create a positive attitude, enhance productivity, improve the standard of living of the workforce and bolster the goal of the organisation. From the extant literature, recent studies have demonstrated that the new pathway to retain employees in the corporate organisation is to duly pay attention to everything that will enhance the QWL of employees (Nanjundeswaraswamy and Beloor, 2022;Biswas and Majumder, 2022). QWL has a greater impact on organisational efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, important to establish research that has been conducted investigating the antecedents of workaholism on the QWL (Atroszko and Atroszko, 2020; Balducci et al , 2022; Spagnoli et al , 2020) and studies investigating predictors of QWL against job performance, work involvement and other several related constructs (Diana et al , 2022; Ehido et al , 2019). Many studies have investigated several antecedents of QWL and this abounds in the literature (Jin and Lee, 2020; Nanjundeswaraswamy and Beloor, 2022), but studies linking QWL with workaholism to the best of knowledge are scanty and rare. More especially, that links it with a psychosocial dimension of brain-drain syndrome.…”
Section: Introductionmentioning
confidence: 99%